Alternatives of synthetic chemicals – chemicals derived from foods and related materials - Lahiri, Susanta (Acta Agraria Debreceniensis, 2018)
Foods are composed of numerous chemicals, each of them work individually or synergistically inside the living organism for a specific reaction supporting the life processes. To date, the efficacy of these chemicals in industrial processes has been explored to a limited extent. In fact, chemicals derived from food have great potential to be used in multi-disciplinary sciences and in numerous applications. Synthetic chemicals might be replaced by the natural resources in the future which will also reduce the environmental impact of hazardous and toxic chemicals. The present article gathers a few examples of chemicals derived from food or related materials and shows how worthy they are in various fields, ranging from radiopharmaceuticals to alternative mining of precious metals. In a nutshell, the article puts forward a few simple ways through which research may adjoin the greener mandates and help in maintaining the sustainability of our environment.